Program CANTIK untuk Peningkatan Pengetahuan dan Sikap dalam Mengonsumsi Tablet Tambah Darah pada Remaja Putri di Kabupaten Bogor: The Influence Of The CANTIK Program On The Knowledge, Attitude, And Behavior Of Adolescent Women In Consumption Blood Added Tablets In Bogor Regency - Wardina Humayrah; Islamiati Putri (Pro Health Jurnal Ilmiah Kesehatan, 2023)
Giving blood supplement tablets (BST) to teenage girls (TG) is a program of the Indonesian government to reduce the prevalence of anemia in 2025. The coverage of giving iron supplementation to TG in West Java Province is still below the national target, especially in high schools in Bogor Regency. Low knowledge and attitudes about anemia prevention are one of the factors for non-compliance in taking BST among TG which affects hemoglobin levels. So the competition for team adolescents in the knowledge of anemia (CANTIK) program was carried out wto compareknowledge, attitudes, and behavior in consuming BST among TG before and after the program. The design of this study is quasi-experimental with one group pre-test-post test. The research subjects were 58 adolescents aged 12-17 years in MTs Al-Islamiyyah, Bogor Regency. Knowledge and attitude were measured through pre and post-questionnaires analyzed in the score range 1-100 and then tested differently using the paired sample T-test. The results showed that there was an increase in the average knowledge score from 39 to 68 while the attitude score from 45 to 77. During the 2 months of the program, the average adolescent consumed BST as much as 6 tablets, with the highest consumption being 20 tablets and the lowest being 0 tablets. There was a significant difference (P<0.05) in knowledge and attitudes about the prevent the other f anemia in taking BST but there was no significant difference in the behavior of TG before and after the program was implemented. Nutrition education through the CANTIK program is quite good at increasing knowledge and attitudes but needs to be continued routinely so that it can change the compliance behavior in taking BST to prevent anemia among TG. Keywords: anemia, blood supplement tablets, cantik, teenage girls ABSTRAK Pemberian Tablet Tambah Darah (TTD) pada remaja putri (rematri) merupakan program pemerintah Indonesia untuk mengurangi prevalensi anemia di tahun 2025. Cakupan pemberian TTD rematri Provinsi Jawa Barat masih di bawah target nasional, khususnya pada SMP/MTs di Kabupaten Bogor. Rendahnya pengetahuan dan sikap tentang pencegahan anemia merupakan salah satu faktor ketidakpatuhan dalam mengonsumsi TTD pada rematri yang memengaruhi kadar hemoglobin. Sehingga program competition for team adolescent in the anemia knowledge (CANTIK) dilakukan dengan tujuan membandingkan pengetahuan, sikap, dan perilaku dalam mengonsumsi TTD pada rematri sebelum dan sesudah program. Desain studi ini adalah eksperimental semu dengan one group pre test-post test. Rematri penelitian adalah rematri berjumlah 58 orang berusia 12-17 tahun di MTs Al-Islamiyyah, Kabupaten Bogor. Pengetahuan, sikap, dan perilaku diukur melalui kuesioner pre dan post lalu dianalisis dalam rentang skor 1-100 dan diuji beda menggunakan paired sample T-test. Hasil menunjukkan bahwa terjadi peningkatan rerata skor pengetahuan sebesar 39 menjadi 68 sedangkan skor sikap dari 45 menjadi 77. Selama program berjalan dalam kurun waktu 2 bulan, rata-rata rematri mengonsumsi TTD sebanyak 6 tablet, dengan konsumsi tertinggi adalah 20 tablet dan terendah 0 tablet. Terdapat perbedaan signifikan (P<0,05) pada pengetahuan dan sikap tentang pencegahan anemia dalam mengonsumsi TTD namun tidak ada perbedaan signifikan pada perilaku rematri sebelum dan sesudah dilaksanakan program. Edukasi gizi melalui program CANTIK cukup baik dalam meningkatkan pengetahuan dan sikap namun perlu dilanjutkan secara rutin agar dapat mengubah perilaku kepatuhan konsumsi TTD untuk pencegahan anemia pada rematri. Kata kunci: Anemia, cantik, tablet tambah darah, remaja putri